2022
DOI: 10.2174/18741495-v16-e220922-2022-30
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Route Selection of Offshore Pipelines Subjected to Submarine Landslides

Abstract: Background: Offshore lifelines (i.e., pipelines and cables) are usually vulnerable to seabed deformations induced by earthquake-triggered geohazards, such as submarine landslides, soil liquefaction, and tectonic faulting. Since the complete avoidance of all areas characterized by offshore geohazards is not always techno-economically feasible, optimal lifeline route selection is deemed necessary for the safety and serviceability of every such infrastructure, in order to minimize the risk of severe environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Geological disasters caused a total of 2008 deaths or missing and direct economic losses of about 27.34 billion yuan [2]. Domestic and foreign scholars have carried out many relevant studies on the slope instability mechanism under the influence of cutting slope excavation and achieved more systematic research results [5,6]. Wen used the thrust transfer coefficient method to study the stability of landslides under the action of groundwater and slope excavation and found that groundwater level is the main factor of landslide instability [7].…”
Section: Introductionmentioning
confidence: 99%
“…Geological disasters caused a total of 2008 deaths or missing and direct economic losses of about 27.34 billion yuan [2]. Domestic and foreign scholars have carried out many relevant studies on the slope instability mechanism under the influence of cutting slope excavation and achieved more systematic research results [5,6]. Wen used the thrust transfer coefficient method to study the stability of landslides under the action of groundwater and slope excavation and found that groundwater level is the main factor of landslide instability [7].…”
Section: Introductionmentioning
confidence: 99%